FAKTOR YANG MEMPENGARUHI MINAT GENERASI Z MEMILIH BUSANA MUSLIMAH - Framesya Nurul Adinda Arzahwa; Suryani Suryani; Prima Priyatno (Politeknik Bisnis Indonesia, 2021)
Interest in Muslim fashion in Indonesia is increasing all the time, this is marked by the election of Indonesia to be ranked fifth according to the Muslim consumer market in the modest fashion category in 2020/2021. This increase in interest is supported by the better quality of clothing and the emergence of well-known brands in the community, especially Generation Z which focuses on fashion and attractive styles. Generation Z likes diverse and innovative fashion products, so it is easy to be attracted to new fashion styles. This study aims to examine the effect of product quality and brand image on the interest of Generation Z in choosing Muslim clothing. The research method uses a quantitative approach with sampling through purposive sampling method which is tested on 100 respondents who use Muslim clothing. The data collection instrument used a questionnaire with a Likert scale. The analytical technique used to determine the magnitude of the effect is multiple linear regression assisted by SPSS version 25. The results of the study conclude that there is a significant influence between product quality and brand image on consumer buying interest. Keywords: brand image, interests, muslim clothing, perception of product quality